2003
DOI: 10.1590/s0100-879x2003001100013
|View full text |Cite
|
Sign up to set email alerts
|

Arachidonic acid triggers an oxidative burst in leukocytes

Abstract: The change in cellular reducing potential, most likely reflecting an oxidative burst, was investigated in arachidonic acid-(AA) stimulated leukocytes. The cells studied included the human leukemia cell lines HL-60 (undifferentiated and differentiated into macrophage-like and polymorphonuclear-like cells), Jurkat and Raji, and thymocytes and macrophages from rat primary cultures. The oxidative burst was assessed by nitroblue tetrazolium reduction. AA increased the oxidative burst until an optimum AA concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 28 publications
2
30
0
Order By: Relevance
“…In phagocytes, AA stimulates superoxide generation, being cytotoxic at physiological and supraphysiological concentrations. 33,34 In addition to stimulating ROS production, 35 the present study provides evidence that FA also decreases the activitiy of catalase in Jurkat and Raji cells. FAs, mainly the PUFAs ones, are also putative targets for free radical propagation, during which lipid peroxides are generated, being deleterious for the tissues.…”
Section: Effect Of A-tocopherol Treatmentsupporting
confidence: 59%
“…In phagocytes, AA stimulates superoxide generation, being cytotoxic at physiological and supraphysiological concentrations. 33,34 In addition to stimulating ROS production, 35 the present study provides evidence that FA also decreases the activitiy of catalase in Jurkat and Raji cells. FAs, mainly the PUFAs ones, are also putative targets for free radical propagation, during which lipid peroxides are generated, being deleterious for the tissues.…”
Section: Effect Of A-tocopherol Treatmentsupporting
confidence: 59%
“…An elevation in superoxide generation increases NOS activity and mRNA levels [34]. Additional studies have shown that the AA release was accompanied by an increased superoxide formation [35,36] and that the PLA 2 inhibitor AACOCF 3 was capable of reducing superoxide formation [36,37]. Therefore, it can be hypothesized that the reduction in nitrite formation following exposure to AACOCF 3 may be mediated by lower levels of superoxide.…”
Section: Discussionmentioning
confidence: 99%
“…Its metabolites are important mediators of intracellular signaling (Cui and Houweling, 2002), inflammation (Pompéia et al, 2003), and immunomodulation (Courrèges et al, 2003). It has also been reported that phosphatidylcholine increases the solubility of cholesterol and can therefore change the composition of fatty deposits and inhibit platelet aggregation, reducing the risk of cardiovascular disease (Mel'Chinskaia et al, 2000).…”
Section: Introductionmentioning
confidence: 99%